Optimization of domestic wastewater treatment through the implementation of the MBBR System - Caylloma - Aquafil - Reyes Araujo, Wilyn (2020)
Caylloma is a district that belongs to the Arequipa region, is located in southern Peru, at an average altitude of 4310 meters above sea level. Caylloma has an activated sludge plant with the capacity to treat up to 200 m3 / d, but given the population increase and low temperatures, bacterial activity is inhibited, which does not guarantee a significant reduction in organic load or bacterial load pathogenic. The research aims to optimize the operation of the domestic wastewater treatment plant. During the investigation, the evaluation, analysis and optimization of wastewater treatment was developed by adding Biocarriers to the two biological reactor tanks, which enabled the activated sludge system to be transformed into a “Moving Bed Biofilm Reactor” -MBBR system -, which consists of the increase of biomass in the reactor tanks, which allows a greater degradation of the organic matter, to obtain an increase of 40% of the total treatment capacity of the plant. At the end of the optimization process there is currently a plant capable of treating an average flow of 280 m3 / d, which covers the requirements of an approximate population of 3200 inhabitantss.